2015
DOI: 10.1002/dmrr.2633
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological predictors of estimated GFR decline in patients with type 2 diabetes and overt proteinuric diabetic nephropathy

Abstract: Our results suggest that not only proteinuria but also tubulointerstitial lesions should be assessed to predict rapid eGFR decline in patients with type 2 diabetes who have overt proteinuria and biopsy-proven diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 24 publications
3
42
0
Order By: Relevance
“…Recently, it has been suggested that tubulointerstitial lesions are more important for predicting the renal prognosis than other types of lesions, such as glomerular and vascular lesions, in not only patients with DN but also, those with other renal diseases (12,27,28). Therefore, more accurate biomarkers of tubulointerstitial injury and inflammation are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been suggested that tubulointerstitial lesions are more important for predicting the renal prognosis than other types of lesions, such as glomerular and vascular lesions, in not only patients with DN but also, those with other renal diseases (12,27,28). Therefore, more accurate biomarkers of tubulointerstitial injury and inflammation are needed.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that the extent of interstitial fibrosis and tubular atrophy (IFTA) was a significant predictor of the renal prognosis, even after adjustment for urinary protein excretion (UP) (12,13). There have also been some other recent reports that stressed the influence of IFTA on the renal prognosis (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…52 Another study 53 including 396 patients with DKD showed that the glomerular classes and scores of interstitial fibrosis and tubular atrophy predict the risk for ESRD or doubling of Scr. 52 Caramori et al 54 measured the renal structures in biopsies obtained from 94 type 1 diabetics without albuminuria. Greater width of the GBM and higher levels of glycated hemoglobin were independently associated with development of diabetic nephropathy.…”
Section: Histological Damagementioning
confidence: 99%
“…Categorical data were analyzed using the chi-squared test across the FZQZ and placebo groups. Since the majority of the patients had primary glomerular disease (PGD), and patients with diabetic nephropathy (DN) with overt proteinuria experience rapid declines in GFR, [12] a subgroup analysis according to CKD-cause (PGD, DN, and others) was performed. Kaplan–Meier methods were used to assess the secondary outcome of time to composite end-point events and their significance was assessed using the log-rank test.…”
Section: Methodsmentioning
confidence: 99%